Encyclopedia of Inorganic and Bioinorganic Chemistry 2005
DOI: 10.1002/9781119951438.eibc0050
|View full text |Cite
|
Sign up to set email alerts
|

Copper: Inorganic & Coordination ChemistryBased in part on the article Copper: Inorganic & Coordination Chemistry by Rebecca R. Conry & Kenneth D. Karlin which appeared in the Encyclopedia of Inorganic Chemistry, First Edition .

Abstract: Copper was one of the first metals used widely because the metal is fairly plentiful (among the 25 most abundant elements in the earth's crust) and can be found in its metallic state. In addition, the metal and its alloys have a number of beneficial qualities including ductility, malleability, strength, corrosion resistance, and high thermal and electrical conductivity, combined with an attractive appearance. Copper is also an essential trace nutrient for organisms ranging from bacteria to mammals. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…56 We attempted to measure the IFE this may cause by titrating Cu 2+ (same preparation and concentrations used in the Cu 2+ →CcSBPII assay) into 10 mM HEPES pH 7.2 without protein and did not observe anything different from titrating the buffer alone (data not shown). Cu + prefers tetrahedral geometries and lower coordination numbers, 57 and our observation that CcSBPII has a low affinity for Zn 2+ , which has a preferred tetrahedral geometry in protein structures, suggests that it is unlikely CcSBPII would specifically bind to Cu + as the major copper species with a KD value (8.54 μM) less than that of Ni 2+ (12.00 μM). Additionally, Cu + requires stabilization through interactions with alkenes and amines.…”
Section: Limitations Of the Methodsmentioning
confidence: 76%
“…56 We attempted to measure the IFE this may cause by titrating Cu 2+ (same preparation and concentrations used in the Cu 2+ →CcSBPII assay) into 10 mM HEPES pH 7.2 without protein and did not observe anything different from titrating the buffer alone (data not shown). Cu + prefers tetrahedral geometries and lower coordination numbers, 57 and our observation that CcSBPII has a low affinity for Zn 2+ , which has a preferred tetrahedral geometry in protein structures, suggests that it is unlikely CcSBPII would specifically bind to Cu + as the major copper species with a KD value (8.54 μM) less than that of Ni 2+ (12.00 μM). Additionally, Cu + requires stabilization through interactions with alkenes and amines.…”
Section: Limitations Of the Methodsmentioning
confidence: 76%
“…In the absence of GSH, the cellular environment may become less reducing, possibly leading to an increased abundance of Cu(II). As a borderline hard acid, Cu(II) exhibits greater affinity for nitrogen- and oxygen-coordinating ligands ( 57 ) which, when coupled with the highly competitive nature of the Cu(II) ion in biological complexes ( 58 ), is likely to greatly increase the incidence of Cu(II) ions interacting with cytoplasmic proteins and perturbing cellular physiology ( 53 55 ). As S. pneumoniae does not appear to possess an alternative thiol pool, these mechanisms provide possible explanations for the severely heightened Cu sensitivity of the Δ copA Δ gshT strain.…”
Section: Discussionmentioning
confidence: 99%
“…7 This strategy critically relies on the fact that Cu(I) and Cu(II) have different coordination properties; the former tend to adopt linear, trigonal, or tetrahedral geometries and bind to highly polarizable ligands, while the latter are stabilized in tetragonal coordination geometries in the presence of weakly polarizable ligands. 8 Initial attempts at leveraging these properties to gate photo-induced CS revealed that the desired photophysical processes were dwarfed by the predominance of unwanted ligand-centered transitions.…”
Section: ■ Introductionmentioning
confidence: 99%